Experimental and Analytical Studies on a Reinforced Concrete Frame Retrofitted with Buckling-Restrained Brace and Steel Caging. Issue 2 (February 2015) - Zhang, Jiaguang; Wu, Bin; Mei, Yang; Shing, P. Benson
A hybrid seismic retrofit scheme, which utilizes a buckling-restrained brace (BRB) to enhance the lateral strength, stiffness and energy dissipation capacity of a seismically-weak reinforced concrete (RC) frame and steel caging to improve the flexural and shear strength of the deficient RC columns and beam-column joints, is proposed. Cyclic quasi-static tests were performed on two half-scale one-story, and single-bay RC frames to evaluate the efficiency of the hybrid retrofit technique. The performance of the BRB, the steel caging, and the connections of the retrofitted frame were studied and found to be satisfactory. The BRB significantly increased the lateral load resistance and energy dissipation capacity of the frame, and the steel caging could effectively change failure mechanism of the RC frame by preventing column failure. Analytical models were developed with OpenSees to simulate the experimentally observed behaviors. Reasonable agreements were achieved between the numerical and experimental results.